Mengembangkan Pemahaman Konsep Perkalian Dan Hasil Belajar Pada Siswa Sekolah Dasar Syamtalira Aron Melalui Pendekatan RME - Asmaul Husna; Samsul Bahri; Nurul Akmal (Tadris Matematika, 2024)
The ability to operate the multiplication of calculation is one of the important competencies that should be the goal of mathematics teaching for elementary school students. The operation of multiplying natural numbers in mathematics learning in elementary schools must be attempted so that it can be mastered well. However, many elementary school students still find that there are still no multiplication calculation operations. The research aims to apply the Realistic Mathematics Education (RME) approach to solving the problem of calculating the multiplication of natural numbers for grade 2 elementary school students. This research is quantitative research. Based on data obtained from the test questions, the ability to understand the concept of multiplication in the first post-test was 87% and in the second post-test 92% of the students completed it, and as many as 37% of students experienced an increase and increase in their understanding of the concept in the high category, 42% in the medium category and 21% in the medium category. low. The results of the research show that the process of increasing understanding of the concept of multiplication increases and student learning outcomes increase.